A Novel Magnetic Coupling to Construct Spiral Deposition of Lithium Ions for Improving Anode Performance of Lithium-Sulfur Batteries. Issue 3 (16th March 2021) - Cao, Yongan; Wu, Qiao; Wang, Wenju; Xia, Zhi; Chen, Yuchao; Zhang, Bo; Zou, Jiaxuan; Zhu, Tianjiao
Abstract : Lithium-sulfur (Li-S) battery is one of the most prospective energy storage devices due to its high specific capacity, low cost and pollution-free reactant. However, the degradation of anode lithium metal and the formation of lithium dendrites seriously shorten the cycle life and reduce its safety. It's a bad obstacle for the application of Li-S batteries. In this work, comparing and analyzing reported applications of the magnetic field simple parallel or perpendicular to the direction of the electric field, one central symmetric and curved magnetic field which is firstly coupled to Li-S batteries has unique advantage. With this magnetic field, lithium ions are subjected to centripetal Lorentz force (FB ), and the trajectory of Li + is transformed from linear aggregation deposition to rotational uniform deposition, inhibiting the formation of lithium dendrites. With 70 mT, the capacity attenuation rate is 0.14%, which is almost a quarter of that with 0 mT. The results of scanning electron microscope (SEM) images show that there are fewer cracks and bulges on the surface of anode with the magnetic field. It can be ascribed to the magnetohydrodynamics (MHD) effect, and the mechanism is also confirmed by the multi-physics field simulation. In summary, this study proves that the central symmetric and curved magnetic field develops a new possibility for mitigating lithium dendrites and improving performance of Li-S batteries.